Terpene-derived, hard-soft block copolymers as sustainable thermoplastic elastomers - Atkinson, Rachel (2021)
The work described in this thesis is focused on the development of sustainable, hardsoft, block copolymers, via reversible addition-fragmentation chain transfer (RAFT) polymerisation. A wide range of terpene (meth)acrylate monomers are investigated, some novel and some previously reported, and a number of block copolymer materials have been produced. The syntheses of these materials are described in detail and some further, application-focused, materials testing has been carried out.